Development of Visual Thinking-Based Fiqh Learning Strategies Using Digital Infographics to Improve Learning Outcomes - Rohman, Miftahur; Ifrohan, Ifrohan (Early Publishing, 2026)
This study aims to develop and examine the feasibility and effectiveness of a visual thinking-based learning strategy using digital infographics in teaching Islamic jurisprudence (fiqh) of prayer to second-grade elementary school students. The research was motivated by the limited ability of students to perform prayer movements sequentially and accurately, indicating a gap between memorization and procedural understanding. This study employed a mixed methods approach with Research and Development (R&D) using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects were second-grade students. Data were collected through needs analysis interviews, classroom observations, expert validation questionnaires, and pretest–posttest assessments. The developed product was validated by material and media experts to ensure content accuracy, visual clarity, and pedagogical appropriateness. The validation results indicated that the digital infographic media met the criteria of high feasibility. The effectiveness test demonstrated a significant improvement in students’ learning outcomes, as reflected in the gain score analysis between pretest and posttest results. The visual thinking strategy facilitated students’ comprehension by presenting prayer concepts in structured visual sequences, enabling better retention and procedural understanding. The integration of visual representation and digital media supports cognitive development at the concrete operational stage and enhances student engagement in religious learning. Therefore, the implementation of visual thinking through digital infographics can serve as an innovative and effective alternative strategy in Islamic religious education at the elementary school level, particularly in improving students’ practical understanding of prayer